A detailed study of combustion characteristics of a DI diesel engine using waste plastic oil and its blends. (15th November 2015) - Kaimal, Viswanath K.; Vijayabalan, P.
Highlights: The physical properties of the fuel greatly affects the combustion characteristics. The engine was able to run on 100% plastic oil without any modifications. PO25 gives almost similar performance characteristics. The peak pressure and heat release for plastic oil and its blends are high. Combustion duration and ignition delay reduces with decrease in blend fraction. Abstract: An experimental investigation was carried out to assess the effects of using plastic oil in a DI diesel engine. Plastic oil was synthesized from plastic waste, collected from municipal landfill areas, by pyrolysis process. PO25 (25% plastic oil and 75% diesel in volume), PO 50 and PO75 blends were prepared using plastic oil and the reference diesel fuel. In this present work the combustion characteristics of a constant speed diesel engine were studied under variable loading conditions. The results indicate that the thermal efficiency of all blends and neat plastic oil is lower than diesel at all loading conditions. At full load, the peak cylinder pressure, heat release, combustion duration and ignition delay of plastic oil and its blends were higher than that of diesel. The peak pressure of the engine running on neat plastic oil was increased by about 6% but it showed poor thermal efficiency. Based on test results it can be noticed that the combustion characteristics are greatly affected by the physical properties of the fuel.